Implementation of the cooperative learning model type decision-making to improve learning outcomes of islamic religious education - Suryanagara Suryanagara (Journal of diversity in learning (JDIL), 2023)
This classroom action research aims to apply a decision-making cooperative learning model to improve student learning outcomes in Islamic religious subjects, specifically classroom action research topics related to the meaning of faith in the Apostles of Allah SWT class XI. The research location was SMA Negeri 4 Kendari, with a total sample of 37 students. This type of research uses classroom action research with the plan, action, observer, and reflection stages. Data collection techniques used multiple-choice tests with test instruments, and data analysis techniques used descriptive analysis. The results of the analysis showed that there was an increase in learning outcomes starting from cycles one and two by applying the cooperative-type decision model. These results indicate that the cooperative decision-making learning model can improve student learning outcomes, especially in Islamic religious education lessons.